A РС-controlled beam scanning system at the technological electron LINAC - Karasyov, S.P.; Pomatsalyuk, R.I.; Tenishev, A.Eh.; Uvarov, V.L.; Shevchenko, V.A.; Shlyakhov, I.N. (Вопросы атомной науки и техники, 2006)
The regulatory documents for a number of technological processes (sterilization and others) require that a continuous control and archiving of beam scanning regime should be provided. To meet these conditions at the radiation-technological facility with the electron linear accelerator LU-10 (10 MeV, 10 kW), an automated complex of scanner control was designed and put into operation. The complex is a CAMAC-based autonomous system controlled by a computer. It provides a programmed control of the beam scanning zone width proceeding from the assigned dimensions of the object under treatment, within 20 to 60 cm, with an automatic setting of the center of the zone in the middle of the object. The complex control also includes the possibility of correcting the position of the beam-scanning center in order to compensate the angle of beam entrance into the scanner electromagnet.